DEBT PAYING ABILITY WITH LIQUIDITY OF SHORT TERM ASSETS IN A BUSINESS - RA. afera ratna wijayanti (IULI Publisher, 2022)
This company is one of the new multinational market research company in Indonesia. The head office in Singapore and has branches in 8 countries including Indonesia, In 2015, this company just started in Indonesia. It is promoting more than 20 brands or clients in different section like health, IT, insurance, banks, food, airline, oral care, hair care, beauty products, laundry products etc. As a local brand they gain consumer’s trust by their quality products. This research applies Financial Performance Evaluation of this market research company, especially for debt paying ability with liquidity of short term. It means how well the company performs for the paying ability as a beginner company in Indonesia. The main data is collected from the audited annual financial reports of the company from 2015 to 2017. Different financial ratios are evaluated by liquidity ratios and account receivable turnover. and finally measure the best performance of the company. The ratios analysis and comparisons are applied for the measurement of several types of financial ratio analysis. Liquidity ratio is conveying the ability to repay short-term creditors and its total cash. It determines the performance of short term creditor of the company under the three categories such as current ratio, quick ratio and cash ratio. Account receivable turnover ratio is measured to know how long the collection of accounts receivable is for one period or how many times the funds embedded in these receivables revolve in one period. I hope this analysis will be helpful for the management of the company who are responsible for taking decisions and formulating plans for future. It will also help the creditors who are the provider of loan capital of the company. They can decide whether they want to extend their loans or not in future. In the conclusion part there are some advice based on their problems which found from the analysis. So this research will show a clear picture about company’s performance on the debt paying ability of short term assets in the last 3 years. Keywords: Financial analysis, ratio analysis, debt paying ability